ANALISIS PELAKSANAAN ASESMEN PERKEMBANGAN BELAJAR ANAK DI TK NEGERI PEMBINA KOTA PEKANBARU - Murni, Rini Anggraini; Chairilsyah, Daviq; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aimed to analyze the re-implementation assessment of the development of children's learning in kindergarten Negeri Pembina Pekanbaru. The research was conducted from January to June in TK Negeri Pembina Pekanbaru. In this study the author uses descriptive research method. The sample in this study were as many as 30 people with engineering samples of Saturated. Data collection techniques used in this study was a questionnaire. Quantitative data analysis in this research is data questionnaire aimed to look at the percentage of the assessment of child development in kindergarten pembinan Pekanbaru. The observation data is processed in the form of numbers that are then incorporated into the arithmetic formula. persetase overall indicator of the assessment results of the analysis of learning development of children in kindergarten Negeri Pembina Pekanbaru is the percentage of 55.33% is obtained pertained criteria